Altered Functional Connectivity and Topological Organization of Brain Networks Correlate to Cognitive Impairments After Sleep Deprivation - Ning Y; Zheng S; Feng S; Li K; Jia H (Nature and Science of Sleep, 2022)
Yanzhe Ning,1– 3 Sisi Zheng,1– 3 Sitong Feng,1– 3 Kuangshi Li,4 Hongxiao Jia1– 3 1The Beijing Key Laboratory of Mental Disorders, Beijing Anding Hospital, Capital Medical University, Beijing, People’s Republic of China; 2The National Clinical Research Center for Mental Disorders, Beijing Anding Hospital, Capital Medical University, Beijing, People’s Republic of China; 3Advanced Innovation Center for Human Brain Protection, Capital Medical University, Beijing, People’s Republic of China; 4Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of ChinaCorrespondence: Hongxiao Jia, The Beijing Key Laboratory of Mental Disorders, Beijing Anding Hospital, Capital Medical University, Beijing, People’s Republic of China, Email jhxlj@ccmu.edu.cn Kuangshi Li, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, 100700, People’s Republic of China, Email likuangshi89@hotmail.comIntroduction: Sleep deprivation (SD) has a detrimental effect on cognitive functions. Numerous studies have indicated the mechanisms underlying cognitive impairments after SD in brain networks. However, the findings based on the functional connectivity (FC) and topological architecture of brain networks are inconsistent.Methods: In this study, we recruited 30 healthy participants with regular sleep (aged 25.20 ± 2.20 years). All participants performed the repeatable battery for the assessment of neuropsychological status and resting-state fMRI scans twice, during the rested wakefulness (RW) state and after 24 h of total SD. Using the Dosenbach atlas, both large-scale FC and topological features of brain networks (ie nodal, global and local efficiency) were calculated for the RW and SD states. Furthermore, the correlation analysis was conducted to explore the relationship between the changes in FC and topological features of brain networks and cognitive performances.Results: Compared to the RW state, the large-scale brain network results showed decreased between-network FC in somatomotor network (SMN)-default mode network (DMN), SMN-frontoparietal network (FPN), and SMN-ventral attention network (VAN), and increased between-network FC in the dorsal attention network (DAN)-VAN, DAN-SMN after SD. The clustering coefficient, characteristic path length and local efficiency decreased after SD. Moreover, the decreased attention score positively correlated with the decreased topological measures and negatively correlated with the FC of DAN-SMN.Conclusion: Our results suggested that the increased FC of DAN-SMN and decreased topological features of brain networks may act as neural indicators for the decrease in attention after SD.Clinical Trial Registration: The study was registered at the Chinese Clinical Trial Registry, registration ID: ChiCTR2000039858, China.Keywords: brain network, functional connectivity, sleep deprivation, cognitive impairment, topological feature